Perceptions of Fishermen Communities Against the Establishment of Conservation Areas in Pongok Island, South Bangka - Catur Pramono Adi; Dian Sutono; Umaroh; Mustasim (Jurnal Airaha, 2019)
Pongok Island is an island that has the potential of coastal ecosystems, namely mangrove, seagrass, and coral reef ecosystems and the presence of fishing by using bombs and potassium which require a management so that mangrove, seagrass, coral reef and fish ecosystems can be utilized sustainably. The management in question is the establishment of a conservation area that involves fishing communities so that an assessment of the community's perception of the determination of conservation areas is needed. This study aims to determine the perception of fishing communities towards the establishment of conservation areas. This research was conducted in December 2014 in Pongok Island, South Bangka. The selection of respondents was done by using purposive sampling. The variables studied are knowledge of conservation, community opinion about conservation location, type of ecosystem that is commonly conserved, knowledge of matters related to the determination of marine conservation, and community support for the determination of conservation areas. The data used are primary data and secondary data. Data analysis used is descriptive analysis to explain the perception of the fishing community towards the determination of conservation areas. The results of the study show that public perception is quite good because the highest percentage of assessment level is found in the assessment criteria agree and strongly agree.